Uniform approximation on ideals of multilinear mappings - Botelho, Geraldo; Galindo, Pablo; Pellegrini, Leonardo (MATHEMATICA SCANDINAVICA, 2010)
For each ideal of multilinear mappings M we explicitly construct a corresponding ideal ^aM such that multilinear forms in ^aM are exactly those which can be approximated, in the uniform norm, by multilinear forms in M. This construction is then applied to finite type, compact, weakly compact and absolutely summing multilinear mappings. It is also proved that the correspondence M ^aM is Aron-Berner stability preserving.